FACTOR ANALYSIS OF PUSH AND PULL TRAVEL MOTIVATION OF FOREIGN TOURISTS TO LOMBOK - Shantika, Made Padmi (University of Surabaya, 2013)
The role of tourism sector in economy is undeniable. It gives a contribution tonational GDP and opens job opportunities for people in its related sectors. Thepotential of tourism in the country are numerous and need to be developed inorder to maximize its contribution to the country. Tourism is growing in someprovinces in the country and it draws attention to study it. This is a descriptiveresearch which used a quantitative approach. This research is aimed to identify thepush and pull travel motivation of foreign tourists in visiting Lombok, thereforethis research adopts a model based on push and pull factors as the conceptualframework. As information has been documented about push and pull travelmotivations to Lombok and factor analysis has been done for analyzing the datawhich may have important marketing implications to the business owners andgovernment.